Opinion formation in social systems: a network model-based simulation study - Mok, Wen Hao (Nanyang Technological University, 2024)
Our opinions are formed through a mixture of personal experiences and the stream of information we encounter daily. However, our opinions are not immutable constructs. The interaction we hold with others as well as external factors can cause our opinions on certain topics to change.